Pengembangan Front-End Website Perpustakaan Politeknik Negeri Jakarta dengan menggunakan Metode User Centered Design - Prawastiyo, Cerah Ayunda; Hermawan, Indra (LPPM STT Terpadu Nurul Fikri, 2020)
The use of the internet in Indonesia, especially in educational institutions, especially universities, relies on the internet to find a collection of information and references related to courses. One of the units in a university that uses the internet by utilizing a website-based information system is the Jakarta State Polytechnic library (PNJ). Website plays an important role for agencies as a good website reference one of which can be assessed in terms of User Interface (UI) that has an attractive look and User Experience (UX) to improve the convenience of website users. In the development of front end website libraries using the User Centered Design (UCD) method,, bootstrap framework, HTML5 programming language, CSS and Javascript. At the design evaluation stage in the form of a wireframe using the System Usability Scale (SUS) method, getting score is 83, blackbox testing to measure website functionality gets results in accordance with the scenario, User Experience Questionnaire(UEQ) testing to measure the comfort level of website users gets positive results.